2007
DOI: 10.1902/jop.2007.060314
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic and Anesthetic Efficacy of 4% Articaine HCl With 1:200,000 Epinephrine and 4% Articaine HCl With 1:100,000 Epinephrine When Administered Intraorally for Periodontal Surgery

Abstract: For patients undergoing periodontal surgery, 4% articaine anesthetic formulations containing epinephrine (1:100,000 or 1:200,000) provided excellent surgical pain control. For patients who can tolerate higher amounts of epinephrine, the 4% articaine 1:100,000 epinephrine formulation had the additional therapeutic advantage of providing better visualization of the surgical field and less bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 12 publications
1
31
1
6
Order By: Relevance
“…Foster et al [17], Kanaa et al [44], Robertson et al [47] and Haase et al [53] concluded that buccal infiltration of the mandibular first molar with 4 % Articaine of 1:100,000 epinephrine will result in a higher success rate than 2 % Lidocaine with 1:100,000 epinephrine, but the duration of pulpal anesthesia will decline over 60 min with either formulation. Tofoli et al [34] and Moore et al [48] reported that 4 % Articaine anesthetic formulations containing epinephrine provided excellent surgical pain control. For patients who can tolerate higher amounts of epinephrine, the 4 % Articaine 1:100,000 epinephrine formulations had the additional therapeutic advantage of providing better visualization of the surgical field and less bleeding.…”
Section: Efficacy Of Articainementioning
confidence: 99%
“…Foster et al [17], Kanaa et al [44], Robertson et al [47] and Haase et al [53] concluded that buccal infiltration of the mandibular first molar with 4 % Articaine of 1:100,000 epinephrine will result in a higher success rate than 2 % Lidocaine with 1:100,000 epinephrine, but the duration of pulpal anesthesia will decline over 60 min with either formulation. Tofoli et al [34] and Moore et al [48] reported that 4 % Articaine anesthetic formulations containing epinephrine provided excellent surgical pain control. For patients who can tolerate higher amounts of epinephrine, the 4 % Articaine 1:100,000 epinephrine formulations had the additional therapeutic advantage of providing better visualization of the surgical field and less bleeding.…”
Section: Efficacy Of Articainementioning
confidence: 99%
“…Moore et al 19 pointed out that 4% articaine with 1 : 100,000 epinephrine had the additional therapeutic advantage of providing better visualization of the surgical field and less bleeding. On the other hand, Santos et al 20 concluded that epinephrine concentration at 1 : 100,000 or 1 : 200,000 in a 4% articaine solution did not affect the clinical efficacy of this local anesthetic for lower third molar extraction with or without bone removal.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, application of chlorhexidine reduced the incidence of alveolar osteitis and episodes of bleeding complications [16]. Barganza et al reported that the intra operative bleeding ranged from 17.80 ± 9.57 ml to 31.93 ± 15.72 ml depending on NSAIDs intake pre-operatively, whereas Moore et al [17,18] described that intra operative hemorrhage ranged from 54.9 ± 36.0 to 70.2 ± 53.0 ml depending on epinephrine concentration in the local anesthetic agent. Buckley et al studied blood loss in periodontal flap surgery using lidocaine 2% with either 1: 50,000 or 1: 100,000 epinephrine.…”
Section: Blood Loss and Dental Surgerymentioning
confidence: 99%
“…However, few sources of error includes variations in the patient's hemoglobin during operation, failure to collect all blood lost from the operative field and instability of hemoglobin that undergoes quick degradation, thus resulting an under estimation of the blood lost. In contrast to the previous methods, this method is expensive, time consuming, technique sensitive and requires trained personnel to carry through the whole procedure accurately [11,18,27,28].…”
Section: Volumetricmentioning
confidence: 99%
See 1 more Smart Citation